Institutional Factors Influencing the Decision to Take Financial Credits among Small Holder Coffee Farmers in Rwanda (International Journal of Scientific Research and Management (IJSRM), 2018)
Though, a lot of emphasis has been put to decentralize financial institutions to offer agricultural credit, access to credit in many rural households in Rwanda remains limited, so far no study done in the study area on institutional factors influencing the decision to take credit. This study investigated the institutional factors influencing the decision to take credit among smallholder coffee farmers in Gisagara District, Southern Province of Rwanda. A Multi stage sampling techniques was employed to select respondents. Primary data were drawn from222 smallholder farmers using structured questionnaires.Binary logistic regression was employed to estimate the data. The results indicated that the institutional factors which influenced access to credit were cooperative membership, extension services, information on credit use, fear take risk and distance to coffee washing station. Based on the findings of the study, recommended that in order to increase access to use agricultural credit there is need to focus in organizing coffee producers in cooperatives, strengthen the current strategies of extension, education and infrastructural services particularly for road transport.